Peranan Masyarakat Dalam Wisata Bisnis Berbasis Sumberdaya Lokal - Lina Asnamawati; Is Eka Herawati; Timbul Rasoki; Ana Nurmalia (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Asnawati L, Herawati IE, Rasoki T, Nurmalia A 2021. The role of community in local resource-based business tourism. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 734-746. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Empowerment is carried out to improve the community's economy. Business tourism has the aim of developing interests and talents in entrepreneurship and helping provide insight to business tourism participants. Areas that have business tourism will affect the economy, overcome unemployment, and preserve the nature and culture of the community. Institutional training and business tours are carried out in various places. One of them is in Tegal Waru Village, Bogor. The research method used in this study is a survey method. The benefits of research are to identify the role of the community in local resource-based business tourism, training activities for the people of Tegal Waru Village and people from other regions. This research is a type of qualitative research with the aim of describing the problems in the research area descriptively. The results of the study indicate that the Kampoeng Wisata Bisnis Tour program is a program to hone the business spirit and understanding of a home industry-based product. The program provided by Kuntum Organizer apart from enjoying the rural atmosphere, visitors are also given the necessary training such as training on making nata de coco, bag making, catfish cultivation, handicrafts, and so on in Tegal Waru Village. Training activities and business tours are carried out based on local resources, where visitors are given direct training by home industry craftsmen